Child and Parenting Outcomes After 1 Year of Educare. Issue 5 (8th February 2017) - Yazejian, Noreen; Bryant, Donna M.; Hans, Sydney; Horm, Diane; St. Clair, Lisa; File, Nancy; Burchinal, Margaret
Abstract : Educare is a birth to age 5 early education program designed to reduce the achievement gap between children from low‐income families and their more economically advantaged peers through high‐quality center‐based programming and strong school–family partnerships. This study randomly assigned 239 children (< 19 months) from low‐income families to Educare or a business‐as‐usual control group. Assessments tracked children 1 year after randomization. Results revealed significant differences favoring treatment group children on auditory and expressive language skills, parent‐reported problem behaviors, and positive parent–child interactions. Effect sizes were in the modest to medium range. No effects were evident for observer‐rated child behaviors or parent‐rated social competence. The overall results add to the evidence that intervening early can set low‐income children on more positive developmental courses.